1998
DOI: 10.1038/sj.bjp.0701951
|View full text |Cite
|
Sign up to set email alerts
|

Role of endogenous nitric oxide in allergen‐induced airway responses in guinea‐pigs

Abstract: 1 Endogenous nitric oxide (NO) can be detected in exhaled air and accumulates in in¯amed airways. However its physiological role has not been fully elucidated. In this study, we investigated a role for endogenous NO in allergen-induced airway responses. Sensitised guinea-pigs were treated with N G -nitro-L-arginine methyl ester L-NAME (2.0 mM) or aminoguanidine (AG) (2.0 mM) 30 min before the allergen challenge, and 3 and 4 h after the challenge. Alternatively, L-arginine (2.4 mM) treatment was performed 30 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
21
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 50 publications
4
21
1
Order By: Relevance
“…We compared the effect of the nonselective NOS inhibitor, L-NAME, with the selective iNOS inhibitor, 1400W in a model of Sephadex-induced inflammation and found that L-NAME, and not 1400W, inhibit Sephadex-induced lung edema and lung tissue eosinophilia. This result is consistent with other workers who demonstrated that L-NAME reduced Sephadex-induced lung edema in the rat (Andersson et al, 1995) and inhibited antigen-induced airway microvascular permeability and eosinophilia in the guinea pig (Iijima et al, 1998) and eosinophilia in the sensitized and challenged rat (Ferreira et al, 1998). The studies described in this manuscript have taken these findings further by investigating the effects of a selective iNOS inhibitor 1400W, validating its activity in an LPS model of inflammation and testing its effectiveness in two models of eosinophilic lung inflammation.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We compared the effect of the nonselective NOS inhibitor, L-NAME, with the selective iNOS inhibitor, 1400W in a model of Sephadex-induced inflammation and found that L-NAME, and not 1400W, inhibit Sephadex-induced lung edema and lung tissue eosinophilia. This result is consistent with other workers who demonstrated that L-NAME reduced Sephadex-induced lung edema in the rat (Andersson et al, 1995) and inhibited antigen-induced airway microvascular permeability and eosinophilia in the guinea pig (Iijima et al, 1998) and eosinophilia in the sensitized and challenged rat (Ferreira et al, 1998). The studies described in this manuscript have taken these findings further by investigating the effects of a selective iNOS inhibitor 1400W, validating its activity in an LPS model of inflammation and testing its effectiveness in two models of eosinophilic lung inflammation.…”
Section: Discussionsupporting
confidence: 82%
“…First, several studies have implicated a role for the iNOS isoform in allergic inflammation due to the increased gene expression seen following antigen challenge in animal models (Yeadon and Price, 1995;Liu et al, 1997) and the increased iNOS expression seen in diseased versus normal tissues in biopsy studies in man (Hamid et al, 1993). Second, pharmacological data exist, and there seems to be general agreement that nonselective NOS inhibitors reduce allergen-induced eosinophilia in several animal models (Feder et al, 1997;Ferreira et al, 1998;Iijima et al, 1998). However, the data incorporating the use of iNOS inhibitors are very confusing and often conflicting with many investigators using compounds with minimal selectivity for iNOS (Trifilieff et al, 2000), and several studies not demonstrating a dose-response relationship with the compounds used and not benchmarking their data by using nonselective NOS inhibitors (to rule out effects of compounds not due to NOS inhibition) (Koarai et al, 2000;Muijsers et al, 2001).…”
mentioning
confidence: 99%
“…Contrasting findings have been reported with regard to the role of NO in vascular leakage. N G -nitro-L-arginine methyl ester (L-NAME) has been shown to markedly attenuate the acute increase in vascular leakage in the airways in sensitized and challenged guinea-pigs [33] and, in another study, during the late-phase reaction [8]. Conversely, ERJEFA È LT et al [34] reported that topically applied L-NAME produced subepithelial plasma extravasation into the airway lumen of the guinea-pig and, in the rat, it was found that intravenously administered L-NAME increased plasma leakage in the trachea [2].…”
Section: Discussionmentioning
confidence: 99%
“…iNOS is found in epithelial and inflammatory cells of the airways and is induced by exposure to pro-inflammatory cytokines [3,6]. iNOS generates 1,000-fold higher amounts of NO than cNOS and may be responsible for the harmful effects of NO by being involved in plasma exudation (although the role of NO in vascular leakage is controversial), eosinophilic inflammation [7,8] and formation of toxic radicals [1].…”
mentioning
confidence: 99%
“…However, in that study L-NAME was effective in abolishing the allergen-induced eosinophilia 48 h after allergen exposure. Similarly, IIJIMA et al [36] also demonstrated a significant inhibitory effect of L-NAME on late-phase allergen-induced eosinophil influx and airway microvascular permeability in guineapigs, suggesting a role for cNOS in inflammatory cell trafficking 48 h after allergen challenge.…”
Section: Discussionmentioning
confidence: 98%